(untitled) (American Journal of Islam and Society, 1987)
Translation In the name of Allah, Most Gracious, Most Merciful. 102. O ye who believe! Fear God as He should be. . . . Surah 3 208. O ye who believe! Enter into Peace [Islam] Whole-heartedly: . . . Surah 2 135. O ye who believe! Stand out firmly For justice, as witnesses To God, even as against Yourselves, or your parents, Or your kin, . . . Surah 4 267. O ye who believe! Give of the good things Which ye have (honourably) earned, And of the fruits of the earth Which We have produced Surah 2 ...